Ethnomathematics of Pananrang in learning mathematics: Determining auspicious days in the buginese traditional farming system - Pathuddin, Hikmawati; Kamariah, Kamariah (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Mathematics is closely related to daily human activities due to its evolution alongside cultural advancements. However, the subject is considered complex and distant from students' daily experiences. This results in a disconnect between mathematics education and real-life applications. Culture-based learning through ethnomathematics could bridge this gap and make mathematics learning more enjoyable.Aim: This study aimed to explore the use of mathematical concepts in determining auspicious days for farming activities in the Buginese community.Method: This study used a qualitative ethnographic approach.Data were collected through interviews with Pananrang experts to understand the process. Data analysis techniques are carried out through reduction, display, and conclusion. Data validity was ensured through time triangulation by verifying the information obtained from informants over multiple interviews.Results: The results showed that the Buginese people utilized mathematical concepts such as addition, division, and modulo arithmetic in determining favorable days for agriculture.Conclusion: This study found that Pananrang is the Buginese community’s local wisdom used as a reference in the traditional agricultural system. Additionally, the results served as a valuable reference for contextual mathematics learning.